2015
DOI: 10.1161/circinterventions.115.002592
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Intravascular Ultrasound–Guided Chronic Total Occlusion Intervention With Zotarolimus-Eluting Versus Biolimus-Eluting Stent Implantation

Abstract: P ercutaneous coronary intervention (PCI) for chronic total occlusion (CTO) is still challenging, and there are unmet needs even with the availability of drug-eluting stents (DESs). [1][2][3][4] Despite the development of novel techniques and technologies for CTO intervention, the increased clinical and angiographic risk factors accompanying more complex procedures have been associated with worse clinical outcomes. [3][4][5][6] The use of intravascular ultrasound (IVUS) has been recommended as 1 way to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
169
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(176 citation statements)
references
References 28 publications
2
169
1
4
Order By: Relevance
“…However, in two randomized trials, IVUS use was not associated with a reduction of contrast load [18,19]. Although in our study, less contrast was required in IVUS guided CTO PCI attempts, this did not result in lower incidence of contrast induced nephropathy.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, in two randomized trials, IVUS use was not associated with a reduction of contrast load [18,19]. Although in our study, less contrast was required in IVUS guided CTO PCI attempts, this did not result in lower incidence of contrast induced nephropathy.…”
Section: Discussioncontrasting
confidence: 56%
“…In a randomized trial, Kim et al [19] compared the mid-term outcome of 201 CTO patients who underwent IVUS-guided versus angiography-guided stenting. At 12 months, the incidence of MACE (composite of cardiac death, MI, or target vessel revascularization) was lower in the IVUS-guided group (2.6% vs. 7.1%; p=0.035) [19]. However, this latter study was underpowered because of low events rate observed in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT) represent two techniques that provide essential information on preprocedural lesion characteristics (i.e., lesion severity, landing zone, and plaque composition) and the result after stent implantation (i.e., stent expansion and eccentricity, strut apposition, lesion coverage, tissue protrusion, and dissections). A total of 11 randomized controlled trials investigated the effect of IVUS-guided PCI with mixed results (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Of note, studies including patients with an increased complexity [i.e., chronic total occlusion (CTO) or lesion length >28 mm] demonstrated a consistent benefit of IVUS-guided PCI as compared with angiography, mainly driven by a reduction of repeat revascularization for restenosis (MACE at 1 year: CTO-IVUS, 2.6% vs. 7.1%, P=0.035; IVUS-XPL, 2.9% vs. 5.8%, P=0.007) (1,2).…”
Section: What Was Known Before Ilumienmentioning
confidence: 99%
“…A total of 11 randomized controlled trials investigated the effect of IVUS-guided PCI with mixed results (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Of note, studies including patients with an increased complexity [i.e., chronic total occlusion (CTO) or lesion length >28 mm] demonstrated a consistent benefit of IVUS-guided PCI as compared with angiography, mainly driven by a reduction of repeat revascularization for restenosis (MACE at 1 year: CTO-IVUS, 2.6% vs. 7.1%, P=0.035; IVUS-XPL, 2.9% vs. 5.8%, P=0.007) (1,2). In addition, IVUS was instrumental in guiding left main stem PCI in the recent EXCEL and NOBLE left main trials in more than 70% of patients, although these studies were not designed to investigate effects of intracoronary-guided imaging (12,13).…”
Section: What Was Known Before Ilumienmentioning
confidence: 99%